Relative Populations and IR Spectra of Cu38 Cluster at Finite Temperature Based on DFT and Statistical Thermodynamics Calculations - Buelna-García, Carlos Emiliano; Castillo-Quevedo, Cesar; Quiroz-Castillo, Jesus Manuel; Paredes-Sotelo, Edgar; Cortez-Valadez, Manuel; Martin-del-Campo-Solis, Martha Fabiola; López-Luke, Tzarara; Utrilla-Vázquez, Marycarmen; Mendoza-Wilson, Ana Maria; Rodríguez-Kessler, Peter L.; Vazquez-Espinal, Alejandro; Pan, Sudip; et al. (Frontiers in Chemistry, 2022)
The relative populations of Cu38 isomers depend to a great extent on the temperature. Density functional theory and nanothermodynamics can be combined to compute the geometrical optimization of isomers and their spectroscopic properties in an approximate manner. In this article, we investigate entropy-driven isomer distributions of Cu38 clusters and the effect of temperature on their IR spectra. An extensive, systematic global search is performed on the potential and free energy surfaces of Cu38 using a two-stage strategy to identify the lowest-energy structure and its low-energy neighbors. The effects of temperature on the populations and IR spectra are considered via Boltzmann factors. The computed IR spectrum of each isomer is multiplied by its corresponding Boltzmann weight at finite temperature. Then, they are summed together to produce a final temperature-dependent, Boltzmann-weighted spectrum. Our results show that the disordered structure dominates at high temperatures and the overall Boltzmann-weighted spectrum is composed of a mixture of spectra from several individual isomers.